Does Timing of Health and Family Planning Services Matter? Age at First Birth and Educational Attainment in Indonesia - Christoph Strupat (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2014)
This paper examines empirically whether midwifes, as an integral part of the health and family planning programs in Indonesia, are effective in advising young women to delay their first birth and also influence the decision on post-primary school attendance. Using the Indonesian Family Life Survey, I investigate the extent to which the exogenous expansion of a midwife program affects the age at first birth and the number of school years of women. My findings suggest that women who were exposed to a midwife when they have to decide on further school attendance (age 13-20) delay their first birth and also stay longer in post-primary school. According to the average returns of education in Indonesia, I conclude that family planning services provided by midwifes can generate large socioeconomic benefits by allowing young women to postpone their first birth. – – Ab den 1990er Jahren wurden im Rahmen des nationalen Gesundheits- und Familienplanungsprogramms 50,000 Hebammen in viele ländliche Gebiete Indonesiens entsandt. Diese Intervention der indonesischen Regierung hatte neben der Verbesserung der gesundheitlichen Versorgung auch das Ziel, das Alter der ersten Geburt durch die Verbreitung von Informationen und Verhütungsmitteln für Frauen zu erhöhen. Konkret sollten Frauen ihr erstes Kind erst ab dem 20. Lebensjahr bekommen. Das Papier untersucht mit Daten des Indonesian Family Life Survey (IFLS), inwieweit dieses Ziel erreicht wurde. Unter Verwendung eines DiD-Schätzverfahrens zeigen die Ergebnisse der Untersuchung, dass die Intervention das Alter bei der ersten Geburt signifikant erhöht und ein hoher Anteil von Frauen ihr erstes Kind erst nach dem 20. Lebensjahr bekommt. Weiterhin konnte gezeigt werden, dass die betroffenen Frauen länger in weiterführende Schulen gehen und somit die Dienstleistungen der Hebammen indirekt den Bildungsabschluss von Frauen beeinflussen.
Keywords: J13; I12; O12; 330; family planning; midwifes; fertility; education